2014
DOI: 10.1590/s0100-06832014000300016
|View full text |Cite
|
Sign up to set email alerts
|

Tolerância de mamona a zinco avaliada por fluorescência de clorofila e nutrição das plantas

Abstract: A medida da fluorescência de clorofila pode ser uma ferramenta útil para detectar alterações no aparato fotossintético das plantas. Considerando que a detecção precoce da contaminação de zinco em plantas é essencial para o monitoramento ambiental, este trabalho objetivou avaliar o estresse causado por esse nutriente em plantas de mamona (Ricinus communis), utilizando a técnica da fluorescência de clorofila. As alterações provocadas pelo Zn nos pigmentos fotossintéticos e na composição mineral das plantas foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…However, independently of the Zn level tested, this accession showed chlorotic leaves and low growth during the evaluation periods, indicating that it was not adapted to the hydroponic system used, when compared to the other accessions. The observed typical symptoms of inhibition of growth of P. glomerata by excess Zn have also been reported for other species such as Sedum alfredii (Li et al, 2009), Ricinus communis (Marques & Nascimento, 2014), Triticum aestivum (Li et al, 2012) and Zea mays (Alonso-Blázquez et al, 2015).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…However, independently of the Zn level tested, this accession showed chlorotic leaves and low growth during the evaluation periods, indicating that it was not adapted to the hydroponic system used, when compared to the other accessions. The observed typical symptoms of inhibition of growth of P. glomerata by excess Zn have also been reported for other species such as Sedum alfredii (Li et al, 2009), Ricinus communis (Marques & Nascimento, 2014), Triticum aestivum (Li et al, 2012) and Zea mays (Alonso-Blázquez et al, 2015).…”
Section: Resultssupporting
confidence: 74%
“…Sofo et al (2013) observed that the Cd/Cu/Zninduced changes in root morphology of Arabidopsis were caused by a hormonal imbalance, mainly controlled by the auxin/cytokinin ratio. It has been indicated that Zn toxicity depends on plant species and growth stage, and that growth inhibition and biomass reduction are common responses of plants to excess Zn (Li et al, 2009;Li et al, 2012;Marques & Nascimento, 2014;Alonso-Blázquez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Use of the Fr/FFr ratio allowed detection of changes in PSII when plants showed no visual symptoms of toxicity. Therefore, chlorophyll fluorescence is a useful tool for monitoring Pb toxicity in castor bean plants, corroborating results found in studies of Cd toxicity (Silva, Nascimento, Gouveia-Neto, & Silva-Jr., 2012;Marques & Nascimento, 2013;, As toxicity (Stoeva, Berova, & Zlatev, 2004;(Silva et al, 2015), Ni toxicity (Gopal, Mishra, Zeeshan, Prasad, & Joshi, 2002;Mishra & Gopal, 2008), Cu and Hg toxicities (Ventrella, Catucci, Piletska, Piletsky, & Agostiano, 2009), Zn (Cherif et al, 2010;Marques & Nascimento, 2014;Marques et al, 2017) and Pb toxicity (Marques et al, 2017).…”
Section: Chlorophyll Fluorescencementioning
confidence: 99%
“…Biomass production, plant nutritional composition, and biochemical analyzes are often adopted to assess fertilizers' effects on crops (Vassilev et al 2011;Marques and Nascimento 2014;Tiecher et al 2016;Bradfield et al 2017). The chlorophyll a fluorescence technique, for example, is a useful tool for evaluating crop performance under agronomic Communicated by O. Ferrarese-Filho.…”
Section: Introductionmentioning
confidence: 99%
“…The opportunity for early assessment of deficiency or toxicity of elements in plants is one of the main advantages of this technique (Faseela et al 2020). For instance, Marques and Nascimento (2014) reported alterations in the photosynthetic efficiency of castor bean plants exposed to Zn even before phytotoxicity symptoms could be visualized.…”
Section: Introductionmentioning
confidence: 99%